Management of SARS-CoV-2 Omicron Variant Community Screenings in Shanghai, China: A Cross-Sectional Study - Chen K; Xu B; Tang Y; Cao J; Wang R; Tian Y; Gao C; Chu M (Dove Medical Press, 2023)
Keyu Chen,1,* Bin Xu,2,* Yifan Tang,3 Juan Cao,1 Rong Wang,3 Yali Tian,3 Chunhong Gao,3 Ming Chu4 1Department of Thoracic Surgery, Jiangsu Province Hospital and The First Affiliated Hospital of Nanjing Medical University, Nanjing, 210029, People's Republic of China; 2Neurosurgical Intensive Care Unit, Jiangsu Province Hospital and The First Affiliated Hospital of Nanjing Medical University, Nanjing, 210029, People's Republic of China; 3Nursing Department, Jiangsu Province Hospital and The First Affiliated Hospital of Nanjing Medical University, Nanjing, 210029, People's Republic of China; 4Department of Nosocomial Infection, Jiangsu Province Hospital and The First Affiliated Hospital of Nanjing Medical University, Nanjing, 210029, People's Republic of China*These authors contributed equally to this workCorrespondence: Chunhong Gao, Nursing Department, Jiangsu Province Hospital and The First Affiliated Hospital of Nanjing Medical University, 300 Guangzhou Road, Nanjing, Jiangsu Province, People's Republic of China, Tel +862568305379, Email gao22095@163.com Ming Chu, Department of Nosocomial Infection, Jiangsu Province Hospital and The First Affiliated Hospital of Nanjing Medical University, 300 Guangzhou Road, Nanjing, Jiangsu Province, People's Republic of China, Tel +862568306917, Email chuming@njmu.edu.cnBackground: Community screening for SARS-CoV-2 Omicron variant plays a significant role in controlling the spread of infection. However, loopholes may exist in the current management of community screening in Shanghai, China. The objective of this study was to discover loopholes in the management of community screening for SARS-CoV-2 Omicron variant in Shanghai, China and provide targeted solutions.Methods: The cross-sectional study was carried out April 4 to April 30, 2021, among residential committee directors from the Putuo District, Pudong District, and Minhang District of Shanghai, China. Data were collected using a self-designed questionnaire about the management of nucleic acid testing (NAT) sampling in communities through the network platform powered by www.wjx.cn.Results: A total of 203 residential committee directors responded to the survey. Of them, 47.3% were not accepted training and 40.4% were not aware of cross-infection. Comparison among sampling sites and communities, high-risk group contained lower proportion of community training (P = 0.093~0.200), higher awareness of cross-infection (P = 0.039~0.777), more medical workers (P = 0.007~0.724) and more tests performed (P = 0.001~0.992). Larger communities had more medical workers, sampling sites, sampling tables (P = 0.000) and higher awareness of cross-infection (P = 0.009), but lower proportion of community training (P = 0.051).Conclusion: Overall, community training and awareness of infection control were inadequate. Government or institutions should organize the community training and raise the awareness of infection control. Significant differences exist in NAT management patterns between sampling sites, as well as communities of different sizes. Residential community directors minimize high-risk sampling point settings in the future. Special personnel designated by the government or institutions should tour to guide each sampling site.Keywords: community screening, SARS-CoV-2 Omicron variant, management, China